2015
DOI: 10.1002/2015jc010783
|View full text |Cite
|
Sign up to set email alerts
|

Shallow ocean response to tropical cyclones observed on the continental shelf of the northwestern South China Sea

Abstract: Based on observed temperature and velocity in 2005 in northwestern South China Sea, the shallow ocean responses to three tropical cyclones were examined. The oceanic response to Washi was similar to common observations with 2°C cooling of the ocean surface and slight warming of the thermocline resulted from vertical entrainment. Moreover, the wavefield was dominated by first mode near‐inertial oscillations, which were red‐shifted and trapped by negative background vorticity leading to an e‐folding timescale of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
66
1
3

Year Published

2016
2016
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 56 publications
(75 citation statements)
references
References 50 publications
5
66
1
3
Order By: Relevance
“…Observed vertical profiles of the water temperature during Typhoon Damrey at Station A were not available. The temperature profiles observed in a mooring station on the continental shelf of the northwestern SCS (Station B in Figure ) indicated that Typhoon Damrey caused a cooling of 4.5°C in the surface layer and a warming of 1.2°C in the subsurface layer (75 m depth) [ Yang et al ., ], which were comparable to our results in which the surface temperature decreased by 4.0°C while the water temperature at 75 m depth increased by 1.0°C (Figure c).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Observed vertical profiles of the water temperature during Typhoon Damrey at Station A were not available. The temperature profiles observed in a mooring station on the continental shelf of the northwestern SCS (Station B in Figure ) indicated that Typhoon Damrey caused a cooling of 4.5°C in the surface layer and a warming of 1.2°C in the subsurface layer (75 m depth) [ Yang et al ., ], which were comparable to our results in which the surface temperature decreased by 4.0°C while the water temperature at 75 m depth increased by 1.0°C (Figure c).…”
Section: Resultsmentioning
confidence: 99%
“…Typhoon Damrey happened to pass by a mooring station (19°35′N, 112°E) (Station B in Figure ) on the continental shelf of the northwestern SCS. The observed variation of temperature caused by the Typhoon Damrey [ Yang et al ., ] was used to compare with and validate the model results. The daily SST and sea surface Chl a time series during the passage of the typhoon were validated by using daily Tropical Rainfall Measuring Mission (TRMM) Microwave Imager (TMI) SST data (http://www.remss.com/) and Chl a values derived from the Moderate Resolution Imaging Spectroradiometer (MODIS) onboard Aqua (http://oceandata.sci.gsfc.nasa.gov/MODISa/Mapped/Daily/9 km/) and Sea‐viewing Wide Field‐of‐view Sensor (SeaWiFS) (http://oceandata.sci.gsfc.nasa.gov/SeaWiFS/Mapped/Daily/9km/), respectively.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The reasons underlying such large differences in NIOs among the three stations are further explored. Apart from the bottom friction which is the general dominated dissipation factors for the NIOs in this shallow water, the deepened mixed layers and the destruction of the stratification would further weaken the NICs to some extent [ Yang et al ., ]. As noted by Zhu et al .…”
Section: Post‐tc Relaxation Stage Responsesmentioning
confidence: 99%